2016
DOI: 10.5897/ajar2016.11525
|View full text |Cite
|
Sign up to set email alerts
|

Association of on-farm feeds handling practices with fungal growth and Mycotoxin production on feeds in smallholder dairy farms, Nakuru, Kenya

Abstract: Practices used by smallholder dairy farmers for handling of feeds at the farm pose a risk of mycotoxins to dairy animals and dairy products, hence a public health concern. The aim of the study was to document the on-farm practices of handling feeds used by these farmers and how they influence the growth of mycotoxin producing fungi together with prevailing extrinsic conditions. Study involved the use of structured questionnaire for interview of smallholder dairy farmers (n=120) for on-farm feed handling practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Further ascertaining the assertion that low OTA detections may be the norm in South African dairy feeds over the past years [ 17 , 18 , 20 , 21 ], the current study found ( Table 2 ) a 3.9% incidence rate for OTA in the 77 tested samples (mean level: 85.6 µg/kg; maximum level 187.9 µg/kg) with all positives having levels below the 250 µg/kg EC guidance limits specified for cereal-based feeds. While these results are lower than the guidance values, long-term persistent exposure may lead to losses in yield alongside other chronic toxicities in animals [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further ascertaining the assertion that low OTA detections may be the norm in South African dairy feeds over the past years [ 17 , 18 , 20 , 21 ], the current study found ( Table 2 ) a 3.9% incidence rate for OTA in the 77 tested samples (mean level: 85.6 µg/kg; maximum level 187.9 µg/kg) with all positives having levels below the 250 µg/kg EC guidance limits specified for cereal-based feeds. While these results are lower than the guidance values, long-term persistent exposure may lead to losses in yield alongside other chronic toxicities in animals [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…A growing number of studies have in the recent past laid focus on mycotoxin occurrences in South African dairy feeds and feed ingredients [8][9][10][11][12], with limited specifics on smallholder farming systems [13], as reported vastly in other African regions [14][15][16][17][18]. Therefore, having identified for the purpose of this study, mycotoxin-related issues as one of the food safety and quality limiting factors impeding smallholder farmers from progressing to commercial agriculture, this study aimed to provide in-depth data, enabling a more accurate and up-to-date evaluation of mycotoxin occurrences in the South African smallholder dairy farming systems, taking Limpopo and Free State provinces into consideration.…”
Section: Introductionmentioning
confidence: 99%